2017
DOI: 10.1111/ceo.12963
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time measurement of needle forces and acute pressure changes during intravitreal injections

Abstract: Real-time continuous recordings of pressure reveal that an instantaneous intraocular pressure spike occurs during intravitreal injection and appears to be separate from the intraocular pressure spike that occurs during needle insertion. This pressure spike is transient and has not been captured by previous methods of intraocular pressure measurement, which rely on single time point measurements. The clinical significance of this brief intraocular pressure spike is unclear and warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
(73 reference statements)
1
8
0
Order By: Relevance
“…3a) Figure 2c. In comparison with existing IOP data [27], Figure 2d illustrates the consistency between the presented function and the existing data.…”
Section: Cannula and Trocar Insertionsupporting
confidence: 58%
See 2 more Smart Citations
“…3a) Figure 2c. In comparison with existing IOP data [27], Figure 2d illustrates the consistency between the presented function and the existing data.…”
Section: Cannula and Trocar Insertionsupporting
confidence: 58%
“…In all studies published so far, resulting IOP values were often determined for single steps of a specific surgical procedure [1,11,28], and the authors observed a strong surgeon-dependent correlation. Christensen et al [27] investigated the IOP resulting from insertions of 19-to 32-G needles and referenced the applied force. A correlation between the force induced and the resulting pressure is always dependent on the geometry of the instrument and the contact surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 30- and 32-gauge needles require the same force to penetrate scleral tissue (440 and 450 kPa); therefore, the perceived differences in pain are unlikely to be due to an increased pressure required to break the skin. 9…”
Section: Discussionmentioning
confidence: 99%
“…The maximum load was chosen based on medical experience and values expected from the literature [ 17 ]. The test speed was adjusted based on puncture force tests already carried out [ 18 ].…”
Section: Methodsmentioning
confidence: 99%